A Highly Selective 8th Order Band-Pass Filter for Lightning Remote Sensing Applications - et. al., Taha Raad Al-Shaikhli, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently, it has been discovered there was an emission of microwave radiation in advance of the lightning process. Therefore, a lot of researches focus on designing alarm systems that can detect and analyze these radiated signals. The previous designs based on commercial band-pass filters which have low accuracy factor and quite expensive as well as the detected signal were tiny in amplitude, thus higher efficiency filters are needed with a flat frequency response for passed band frequencies between 950 MHz to 1050 MHz in order to avoid the GSM band which generates a high interference to the mentioned detection system. In this research, a band-pass filter has been designed and tested for measurement with a center frequency of 1 GHz and by using Advance Design System (ADS) to be simulated and then fabricated on FR-4 substrate. The measurement came with good compatibility to the simulation results at return loss of -34.747 dB and also the insertion loss of -3.83 dB. This design also works perfectly for the Lightning detection sensor of Narrow Bipolar Event (NBE).